PRICE SETTING BEHAVIOUR IN PAKISTAN: Stylized Facts from Micro SPI Dataset - Fauzia SOHAIL; Ambreen FATIMA (Pakistan Journal of Applied Economics, 2018)
The study analyzes the consumer price behavior by employing the micro-level price data for Pakistan. Substantial heterogeneity in the price setting behavior is observed across various products. The study finds that on an average, 15.8 per cent of prices change every week, with mean (median) duration of 5.8 (4) weeks of price spell. For most commodities, price increase is found more often than the price decrease. On an average, prices are increased by 8.1 per cent and reduced by 7.2 per cent. It reveals a broad spectrum of synchronization across cities ranging from partial staggered to perfect synchronized pricing behavior. The sticky nature of regulated commodities in case of Pakistan is confirmed in the study. Highly significant estimates in the regression analysis proves the existence of elements of both, the state dependent as well as the time dependent factors in determining frequency of the price change in Pakistan.